China–Africa Cooperation: promises, practice and prospects. - Grimm, Sven (Journal of Contemporary China, 2014)
Chinese engagement in African states has increased tremendously over the last decade, much in line with Chinese globalisation strategies and supported by state encouragement and financial support. The size and potential of China as a world power leads to the level of expectations the country faces from the developing world. However, some elements of these expectations are also created through political discourses which emphasise differences with Western countries. The types of promises that the Chinese leadership makes to create such enthusiastic welcome amongst African political leaders are linked closely to the discourse on South–South cooperation. Albeit different from Western development assistance promises and parallel attempts to produce moderate expectations, the current discourse is thus partly sowing the seeds for future disappointment. This article takes a closer look at the discussions around South–South cooperation in China–Africa relations and at key rhetorical features (‘mutual benefit’; ‘non-interference’) and at the practice of this cooperation. It concludes that the Chinese discourse is creating large public expectations in African countries and while China delivers on many projects, its impact on development is less certain. The overall development success of this strategy builds on longer-term success and is implicitly linked to the occurrence of more reforms in Africa. Chinese policy thus ‘bets on the future’ in their foreign relations with Africa; the success of this strategy is dependent on political circumstances among the partners that are largely beyond Chinese control. In a number of cases, it can thus be expected that currently up-beat political rhetoric is going to meet obstacles that will require adjustments in a discourse that, in its current form, might undermine Chinese credibility if not the core elements of South–South cooperation altogether.